Structural changes and compressive behavior of a dystrophic clayey Red Latosol under different use and management systems - Oliveira, Geraldo César de; Junior, Moacir de Sousa Dias; Resck, Dimas Vital Siqueira; Curi, Nilton (Pesquisa Agropecuaria Brasileira, 2003)
One of the consequences of inadequate soil management is its compaction that causes the loss of its sustainability and reduction of its productivity. The objective of this study was to evaluate the structural changes and the compressive behavior of a Latosol (Oxisol) under native vegetation, "Cerrado" (C), no-till (NT) and conventional till (CT) system, after two decades of use. The undisturbed soil samples were used to characterize the soil bulk density, the porous space and to perform the uniaxial compression test. The disturbed soil samples were used for soil physical and chemical characterization analyses in the analyzed depth. The bulk density varied in the following order: NT = CT > C (0 to 5 cm) and CT > NT > C (20 to 30 cm). Organic matter data showed that in the C = NT > CT (0 to 5 cm) and C = NT = CT (20 to 30 cm), showing the NT capacity of increasing organic matter. The preconsolidation pressure changed in the following order: NT = C > CT (0 to 5 cm; tension -1,500 kPa), and CT > C = NT (20 to 30 cm; tension -1,500 kPa).